As dimensões ensino e pesquisa enquanto premissas institucionais da formação acadêmica no arquipélago Universidade Federal do Pará - OLIVEIRA, Damião Bezerra (2007)
We deal about the relation between teaching and research as essential characteristic of the modern conception of university instituted and its repercussions in the understanding of academic teaching, establishing the education while comparative particularity to be understood in this totality. With the thus defined subject, the tensions of this academic ideal in its institutionalization in Brazil is examined, after that in the UFPA and Center of Education. The problem of research is express in three basic questionings: How was instituted the research in the Brazilian academic space and which its repercussions in the characterization of the teaching activity in this institution? How teaching and research dimensions are represented in official documents of the UFPA? How this relation happens in the particularity of the Center of Education? This problematic one consists from a philosophicalepistemological boarding where the concepts of practical, productive and theoretical rationality and of scientific and social institution had been the conducting wires. In an effort of description-conceptual understanding of the subject, the inquiry was leaned over on bibliographical sources and registers of qualitative character, but also of statistical information regarding the UFPA and Center of Education. To the set of selected sources if explanation applied procedures of literal analysis basically -, commentary and dissertation. It was possible to understand the specificity of the complexity and heterogeneity of the research of the knowledge and education notions that there were institute in the Brazilian university, the tensions instituted and the particularities that assume in the educational field. These conceptual elements also appear in the official documents that define the objectives and the structure of UFPA and Center of Education, still that the conditions of achievement of this instituted ideal only come if presenting in well recent years.